Composition and Stress Analysis in Si/SiGe Structures - MOORE, ROBERT; PEROVA, TANIA (IEEE, 2004)
Strained Si tecbnology enables improvements in CMOS performance and functionality via replacement of the bulk, cubic-crystal Si substrate witb a Si substrate that contains a tetragonally distorted, biaxially strained Si thin f h at the surface. Here we use micro-Raman spectroscopy to enable us to characterise growth processes of strained silicon, and to characterise the resulting level of strainlstress in the silicon and the effect it has on the underlying layer of graded SiGe.
Proceedings of IEEE 1st International Conference
PUBLISHED
ISBN 0-7803-8532-2
Acapulko, Mexico
Keywords: Electronic & Electrical Engineering